Compact Two-Color Pr3+-Doped ZBLAN Fiber Lasers. Issue 4 (3rd September 2017) - Wu, Duanduan; Cai, Zhiping; Xu, Huiying
ABSTRACT: Two-color laser simultaneous oscillation in compact trivalent praseodymium ion (Pr 3+ )-doped ZrF4 -BaF2 -LaF3 -AlF3 -NaF (ZBLAN) fiber lasers is investigated. Fiber pigtails by coating high-reflective visible dielectric films are utilized as fiber mirrors (FMs) to construct compact all-fiber laser cavity. Reflectance/transmittance of FMs is intentionally designed to balance net gains and reduce gain competition of different lasable wavelengths in the constructed fiber lasers. By using two selected FMs with high reflectivity at green-light and low reflectivity at red-light, simultaneous green and red laser emission in all-fiber Pr 3+ -doped ZBLAN fiber laser is obtained. Moreover, simultaneous orange and red laser emission is also achieved with another selected FM of high reflectivity at orange-light and low reflectivity at red-light. Our work will provide an effective and easy method to construct compact special fiber (e.g., ZBLAN fiber, chalcogenide fiber) lasers.